A self-assembly preparation method of nanoporous gold based on twinned gold nanospheres
Through the self-assembly technology of twin gold nanospheres, the environmental pollution and complex process problems in the existing nanoporous gold preparation methods are solved, and the preparation of nanoporous gold that is green and environmentally friendly, simplified processes and reduced costs is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202111550787.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-17
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-12-17
AI Technical Summary
The existing preparation methods of nanoporous gold have problems such as environmental pollution, complex processes and high costs, and it is difficult to meet the needs of industrial production.
The self-assembly technology of twin gold nanospheres is adopted to prepare twin gold nanosphere sol seed crystals by chemical reduction method, and the reduction reaction is performed by alternately adding tetrachloroauric acid and sodium citrate solutions to make the grains grow, and finally the self-assembly and growth of gold particles is achieved under the action of centrifugal force to prepare nanoporous gold.
The green and environmentally friendly preparation of nanoporous gold is realized, the process flow is simplified, labor costs are reduced, and it is suitable for large-scale industrial production, and the pore size of nanoporous gold can be adjusted.
Smart Images

Figure CN116265156B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano material structure design, and in particular to a method for growing nano porous gold (NPG) by self-assembly of twinned gold nanoparticles. Background Art
[0002] Nanoporous metals are metallic materials with nanometer-sized pores. Their extremely high specific surface area makes them have great application prospects in catalysis, biosensing, surface Raman enhancement, etc. In recent years, the field of nanoporous metals has experienced accelerated development because of the high specific surface area, well-defined pore size, functional sites and a wide range of functional properties of these materials. Nanoporous gold is undoubtedly the most attractive system in the class of nanoporous metals: in addition to the feasibility of preparation, it also combines multiple desirable properties, such as the occurrence of surface plasmon resonance, huge specific surface area, electrochemical activity, biocompatibility, etc. All these characteristics are consistent with the development of NPG as an efficient and multifunctional sensing platform. In this regard, NPG-based sensors show excellent sensitivity and selectivity for a wide range of analytes from molecules to biomolecules (until single molecule detection), and the huge surface area / volume ratio has been shown to be the key to determine these properties. Due to these characteristics, NPG-based Raman sensors are finding applications in medical, biological and security fields (such as medical diagnosis and monitoring processes).
[0003] At present, the preparation of nanoporous gold is mainly dealloying, and the specific preparation methods are divided into two types: chemical dealloying and electrochemical dealloying. Dealloying is a corrosion process in which the alloy is physically separated by selectively dissolving the most electrochemically active alloy component, so that a porous sponge composed mainly of more noble alloy components is formed. The dealloying process can be carried out by using two different pathways, namely electrochemical dealloying and chemical dealloying. First, the order of dissolution is based on the electrochemical activity of the metals in the alloy. In this series, gold is the worst electrolytic metal that can be electrochemically dissolved, such as Au-Ag alloy, Au-Zn alloy and Au-Li alloy, etc. The porous structure can be adjusted according to the proportion of alloy metals. In contrast, chemical dealloying, also known as chemical etching, is based on the chemical activity of the metal, especially gold is chemically stable in all acids or alkalis, while silver (Ag), aluminum (Al) and copper (Cu) are easily dissolved. In addition, the morphology of the precursor affects the form of dealloying (for example, nanoparticles, nanowires, microwires and films). In these two dealloying methods, the main advantage is that the pore size can be controlled and the surface is uniform (especially all pores have the same size), while the main disadvantage is the harsh conditions required for chemical dealloying (such as nitric acid HNO3, sulfuric acid H2SO4 or sodium hydroxide NaOH, etc.) or the influence of electrolyte composition on the electrochemical dealloying method. The use of these toxic and irritating acidic or alkaline chemical reagents inevitably leads to environmental pollution; moreover, the cumbersome chemical or electrochemical production process is time-consuming and labor-intensive, resulting in high labor costs for the preparation of nanoporous gold, which is not conducive to industrial production. In addition, nanoporous gold prepared by chemical or electrochemical methods will inevitably be contaminated by the chemical reagents used. Summary of the invention
[0004] In order to overcome the shortcomings of the existing preparation technology of nanoporous gold, the purpose of the present invention is to use the self-assembly technology of gold nanotwins to provide a method for preparing nanoporous gold that is simple, convenient and environmentally friendly.
[0005] Specifically, the present invention provides a method for preparing nanoporous gold based on the self-assembly growth of twinned gold nanospheres, comprising the following steps: (1) preparing twinned gold nanosphere sol seed crystals: using tetrachloroauric acid solution and sodium citrate solution as raw materials, preparing the twinned gold nanosphere sol seed crystals by chemical reduction; (2) twinning growth: continuing to alternately add tetrachloroauric acid solution and sodium citrate solution raw materials to the twinned gold nanosphere sol seed crystals prepared in step (1) for reduction reaction, so that the grains grow to a desired size, thereby obtaining gold sol; (3) self-assembly growth of gold particles: centrifuging the gold sol prepared in step (2), and allowing the grains to self-assemble and grow under the action of centrifugal force, thereby obtaining the nanoporous gold.
[0006] like Figure 1 As shown in FIG, twinned gold nanoparticles with a diameter of 13 to 16 nm are first prepared by chemical reduction, and then the gold particles continue to grow gradually by chemical reduction, with an average growth of about 2 nm each time. Figure 2 As shown in FIG. 1 , the obtained gold nanospheres have a multi-twin structure, and the exposed crystal faces of all particles are (111) faces. Exposing the same crystal faces is conducive to self-assembly in the subsequent steps. Figure 3 As shown, the obtained twin gold nanosphere sol self-assembles under centrifugal force to grow a three-dimensional porous structure, and finally obtains a nanoporous gold sheet with a diameter of 2 to 4 mm.
[0007] Preferably, the preparation of the twinned gold nanosphere sol seed crystals comprises the following steps: adding tetrachloroauric acid solution to boiling deionized water under stirring conditions, continuing to heat to boiling, then dripping sodium citrate solution, continuing heating and boiling for 30 to 40 minutes, and naturally cooling to obtain twinned gold nanosphere sol seed crystals with a grain diameter of 13 to 16 nm.
[0008] Preferably, in the process of preparing the twin gold nanosphere sol seed crystals, the concentration of the tetrachloroauric acid solution is 0.2-0.4 g / 100 ml, and the amount added is 5-10 ml; the concentration of the sodium citrate solution is 0.5-1.5 wt %, and the amount added is 4-5 ml.
[0009] Preferably, the twinning growth comprises the following steps: (1) stirring and heating the twinned gold nanosphere sol seed crystal to 85-95° C., then adding sodium citrate solution and tetrachloroauric acid solution, and continuing stirring and heating for 10-20 minutes; (2) repeating step (1) 6-10 times to obtain a gold sol with a grain size of 25-35 nm.
[0010] Preferably, during the twin growth process, the concentration of the sodium citrate solution is 0.5-1.5wt%, and the amount added each time is 1-3ml; the concentration of the tetrachloroauric acid solution is 20-30mmol / L, and the amount added each time is 0.5-2ml.
[0011] Preferably, the self-assembly growth of gold particles comprises the following steps: adding gold sol into centrifuge tubes respectively, and centrifuging at a speed of 9000-12000 r / min for 8-20 minutes to allow the gold nanoparticles to self-assemble and grow to obtain nanoporous gold with a diameter of 2-4 mm.
[0012] like Figure 3 As shown, the gold nanotwins rotate, collide and rearrange under the action of centrifugal force until the same crystal faces overlap together, and the particles combine to achieve self-assembly. The obtained nanoporous gold sheets are washed with deionized water and stored in anhydrous ethanol.
[0013] Beneficial Effects
[0014] (1) The method of the present invention does not require any template or dealloying process, thus overcoming many defects of the traditional preparation method of nanoporous gold, such as the pollution caused by chemical and electrochemical corrosion during dealloying. The solution disclosed by the present invention is more environmentally friendly;
[0015] (2) The method of the present invention greatly simplifies the preparation process of nanoporous gold. It only needs to mechanically centrifuge the gold sol to make it self-assemble and grow, which greatly shortens the preparation time and is suitable for large-scale and batch industrial production.
[0016] (3) The method of the present invention can adjust the pore size of nanoporous gold by controlling the size of twin particles and the mechanical rotation speed;
[0017] (4) The porous gold sheet prepared by the method of the present invention has a fixed geometric shape and is a regular round sheet, which is suitable for production, storage and practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the statistical result diagram of the size of gold nanoparticles after each growth;
[0019] Figure 2 Transmission electron microscopy image of the grown gold nanospheres with multiple twin structures;
[0020] Figure 3 Schematic diagram of the self-assembly growth of nanoporous gold by twinned gold particles;
[0021] Figures 4 to 9 The morphology scanning electron microscope images of the nanoporous gold prepared in Examples 1 to 6 are respectively;
[0022] Fig.10 This is a scanning electron microscope image of the morphology of the gold nanospheres after self-assembly prepared in Comparative Example 1;
[0023] Fig.11 This is a transmission electron microscopy image of the gold nanospheres obtained in step (2) of Comparative Example 2;
[0024] Fig.12 This is a scanning electron microscope image of the morphology of the gold sol sample obtained in step (3) in Comparative Example 2. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific examples, but the protection scope of the present invention is not limited to the contents described.
[0026] The present invention provides a method for preparing nanoporous gold which is simple, convenient and environmentally friendly. Figure 3As shown in the schematic diagram, twin gold nanoparticles with a diameter of about 13 to 16 nm are first prepared by chemical reduction, and then the gold particles continue to grow gradually by chemical reduction, each time growing about 2 nm. Before and after the growth, the exposed crystal faces of the twin gold nanospheres are all (111) faces. Figure 3 As shown, the final twinned gold nanosol self-assembles under the action of centrifugal force and grows a three-dimensional porous structure.
[0027] The principle of self-assembly is based on the self-assembly of isotropic rigid particles. Gold nanotwins are a type of isotropic rigid particles. Their self-assembly is based on entropy-driven recrystallization. The resulting crystal state is thermodynamically stable. The increase in free volume entropy is because the solvent molecules gain the maximum degree of freedom after the regular accumulation of colloids. By applying a certain centrifugal force, the twin particles in the colloid collide, rotate, and rearrange until the same twin faces overlap, and the particles self-assemble. A large number of twin particles self-assemble to form a three-dimensional porous structure. As time goes on, the number of particles filled controls the size of the three-dimensional pores.
[0028] Compared with traditional porous gold preparation, this method does not require any template or dealloying process, overcoming many defects of traditional preparation methods of nanoporous gold. It not only greatly shortens the preparation time, but also avoids pollution caused by chemical and electrochemical corrosion during dealloying.
[0029] First, the seed crystal can be prepared by the following method using tetrachloroauric acid solution and sodium citrate solution as raw materials: for example, 90 ml of deionized water is added to a three-necked flask, heated to boiling under mechanical stirring, and then 5 to 10 ml of tetrachloroauric acid solution with a concentration of 0.2 to 0.4 g / 100 ml is added, and then 4 to 5 ml of sodium citrate solution with a concentration of 0.5 to 1.5 wt% is added dropwise, and the heating and boiling are continued for 30 to 40 minutes, and finally the twinned gold nanosphere sol seed crystal with a diameter of about 13 to 16 nm is obtained by natural cooling. The obtained multiple twins expose the same crystal plane, which is (111) plane. The same crystal plane is combined under the driving force of centrifugal force, and it is easier to achieve self-assembly. Among them, if the concentration of tetrachloroauric acid and sodium citrate solution is too low, the synthesis efficiency of gold nanospheres will be low and the particle concentration will be too low; and if the concentration of tetrachloroauric acid and sodium citrate solution is too high, the concentration of gold nanospheres will be too high, and the particles will agglomerate prematurely when used for subsequent particle growth.
[0030] Next, the seed crystals obtained in the above steps continue to grow twins: the obtained twin gold nanosphere sol seed crystals are kept at 85-95°C, and then 1-3 ml of a sodium citrate solution with a concentration of 0.5-1.5wt% and 0.5-2 ml of a tetrachloroauric acid solution with a concentration of 20-30mmol / L are quickly added, and the stirring and heating are continued for 10-20 minutes. Repeat this step 6-10 times, and the grains grow by about 2nm each time, and finally a gold sol with a grain size of 25-35nm is obtained. Among them, if the ratio of tetrachloroauric acid to sodium citrate is too small, only ellipsoidal nanoparticles can be obtained; if the ratio of tetrachloroauric acid to sodium citrate is too large, the size distribution of the obtained spherical particles will be uneven, the size distribution will be widened, the large particles will be larger, and the small particles will be smaller.
[0031] Finally, the gold particles are self-assembled and grown: using the grown gold sol as the raw material, 30 ml of gold sol is added to each centrifuge tube, and the gold nanoparticles are self-assembled and grown at a speed of 9000-12000 r / min. The gold nanotwins rotate, collide and rearrange under the action of centrifugal force until the same crystal faces overlap together, and the particles are combined to achieve self-assembly. After 8-20 minutes, the centrifugation is ended to obtain gold flakes with a diameter of about 2-4 mm, that is, nanoporous gold is successfully obtained. The obtained nanoporous gold flakes can be washed with deionized water and stored in anhydrous ethanol.
[0032] The gold nanoparticles prepared by the method disclosed in the present invention have a multiple twin structure, and the crystal faces exposed by the twins are all (111) faces, so under the drive of centrifugal force, self-assembly is easier to achieve when the same crystal faces are combined.
[0033] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0034] Example 1
[0035] (1) Add 90 ml of deionized water to a three-necked flask and heat it in an oil bath. Heat it to boiling under mechanical stirring. Add 5 ml of a 0.2 g / 100 ml tetrachloroauric acid solution to the boiling solution. Continue to heat the solution to boiling. Then, dropwise add 4 ml of a 0.5 wt % sodium citrate solution. Continue heating and boiling for 30 min. Finally, cool naturally to obtain seed crystals with a grain diameter of 13 nm.
[0036] (2) Using the gold sol obtained in step (1) as seed crystals, the boiling solution was cooled to 85°C and then kept warm in an oil bath, stirred continuously and the temperature was maintained constant, then 1 ml of a 0.5 wt% sodium citrate solution and 0.5 ml of a 20 mmol / L tetrachloroauric acid solution were quickly added, and the mixture was stirred and heated continuously for 10 minutes.
[0037] (3) While maintaining the stirring and the temperature of the sol unchanged, step (2) was repeated 6 times to finally obtain a gold sol with a grain size of 25 nm.
[0038] (4) Using the gold sol grown in step (3) as raw material, 30 ml of gold sol was added to each centrifuge tube, and the sol was divided into four tubes. The gold sol was centrifuged at a speed of 9000 r / min for 8 min to allow the gold nanoparticles to self-assemble and grow, and a gold sheet with a diameter of 2 mm was obtained. The obtained nanoporous gold sheet was washed with deionized water and stored in anhydrous ethanol. Figure 4 As shown, the nanoporous gold sheet is initially obtained.
[0039] Example 2
[0040] In this embodiment, the other steps are the same as those in embodiment 1, wherein in step (4), the centrifuge speed is increased to 10000 r / min and the centrifugation time is changed to 12 minutes. Figure 5 As shown, nanoporous gold with good surface density and regular nanopore size was obtained.
[0041] Example 3
[0042] In this embodiment, the other steps are the same as those in embodiment 1, wherein the subsequent growth temperature of the seed crystal is increased to 90°C, the centrifuge speed is increased to 10000 r / min, and the centrifugation time is changed to 12 minutes. Figure 6 As shown, nanoporous gold with good surface density, regular nanopore size and good uniformity is obtained.
[0043] Example 4
[0044] (1) Add 90 ml of deionized water to a three-necked flask and heat it in an oil bath. Heat it to boiling under mechanical stirring. Add 10 ml of 0.315 g / 100 ml tetrachloroauric acid solution to the boiling solution. Continue heating the solution to boiling. Then, dropwise add 4.5 ml of 1 wt % sodium citrate solution. Continue heating and boiling for 40 min. Finally, cool naturally to obtain seed crystals with a grain diameter of 15 nm.
[0045] (2) Using the gold sol obtained in step (1) as seed crystals, the boiling solution was cooled to 90°C and then kept warm in an oil bath, with continuous stirring and the temperature maintained constant. Then, 2 ml of a 1 wt% sodium citrate solution and 1 ml of a 25 mmol / L tetrachloroauric acid solution were quickly added, and the mixture was heated with continuous stirring for 15 minutes.
[0046] (3) Keeping the stirring and the temperature of the sol constant, repeat step (2) 8 times to finally obtain a gold sol with a grain size of 28 nm.
[0047] (4) Using the gold sol grown in step (3) as raw material, 30 ml of gold sol was added to each centrifuge tube, and the sol was divided into four tubes. The gold sol was centrifuged at a speed of 11000 r / min for 15 min to allow the gold nanoparticles to self-assemble and grow, and a gold sheet with a diameter of 3 mm was obtained. The obtained nanoporous gold sheet was washed with deionized water and stored in anhydrous ethanol. Figure 7 As shown, the surface of the obtained nanoporous gold sheet is smooth and flat, the density and uniformity of the nanopores are good, and the size of the nanopores is regular, about 200 to 300 nm.
[0048] Example 5
[0049] In this embodiment, the other steps are the same as those in Example 4. In step (1), the concentration of tetrachloroauric acid is increased to 0.4 g / 100 ml, and the concentration and amount of sodium citrate are increased to 1.5 wt% and 5 ml, respectively. In step (2), the seed crystal growth temperature is increased to 95°C, the concentrations of sodium citrate and tetrachloroauric acid are increased to 1.5 wt% and 30 mmol / L, respectively, and the amounts of sodium citrate and tetrachloroauric acid are increased to 3 ml and 2 ml, respectively. The number of growth times is changed to 9 times, the centrifuge speed is increased to 12000 r / min, and the centrifugation time is changed to 18 minutes. Figure 8 As shown, the surface of the obtained nanoporous gold sheet is smooth and flat, the density and uniformity of the nanopores are good, and the size of the nanopores is regular, about 100 to 200 nm.
[0050] Example 6
[0051] In this embodiment, the other steps are the same as those in embodiment 5, and the centrifuge speed is reduced to 9000 r / min. Fig. 9 As shown, the surface of the obtained nanoporous gold sheet is smooth and flat, the nanopore density and uniformity are good, the nanopore size is regular, and the nanopore size is about 100 nanometers.
[0052] Comparative Example 1
[0053] (1) Add 90 ml of deionized water to a three-necked flask and heat it in an oil bath. Heat it to boiling under mechanical stirring. Add 5 ml of 0.2 g / 100 ml of tetrachloroauric acid solution to the boiling solution. Continue to heat the solution to boiling. Then, dropwise add 10 ml of 1 wt % sodium citrate solution. Continue heating and boiling for 30 min. Finally, cool naturally to obtain seed crystals.
[0054] (2) Using the gold sol obtained in step (1) as seed crystals, the boiling solution was cooled to 85°C and then kept warm in an oil bath, stirred continuously and the temperature was maintained constant, then 1 ml of a 0.5 wt% sodium citrate solution and 0.5 ml of a 10 mmol / L tetrachloroauric acid solution were quickly added, and the mixture was stirred and heated continuously for 10 minutes.
[0055] (3) Keep stirring and the temperature of the sol constant, repeat step (2) 6 times, and finally obtain gold sol.
[0056] (4) Using the gold sol grown in step (3) as a raw material, 30 ml of gold sol was added to each centrifuge tube, and the centrifuge was performed at a speed of 5000 r / min for 8 min to allow the gold nanoparticles to self-assemble and grow. No corresponding porous gold sheet was obtained, but only concentrated gold sol was obtained. The concentrated gold sol was washed with deionized water and stored in anhydrous ethanol.
[0057] like Fig.10 As shown in the morphology of the obtained gold sol under a scanning electron microscope, the gold nanospheres aggregated and partially self-assembled, but failed to successfully assemble into a porous three-dimensional structure. The main reason is that the concentration of the prepared gold nanospheres is too low and the centrifugal speed is too low.
[0058] Comparative Example 2
[0059] (1) Prepare 5 mL of HAuCl4 (1 wt%) solution, add 90 mL of ultrapure water, heat the solution to 100°C in an oil bath under reflux conditions and stir continuously, then quickly add 5 mL of sodium citrate solution (1 wt%) and continue stirring. At this time, the color of the solution gradually changes from light yellow to colorless. About two minutes after the addition, the solution will appear brown-black and quickly turn into wine red. After the solution turns into wine red, continue heating for 15 minutes.
[0060] (2) The mixed solution in step (1) was cooled to 90°C, and 5 mL of HAuCl4 (1 wt%) solution and 5 mL of sodium citrate solution (1 wt%) were added again, and stirring was continued for 30 min. Then, the mixture was cooled to room temperature and washed three times with deionized water to obtain gold nanospheres.
[0061] (3) The gold nanospheres obtained in step (2) were centrifuged at a speed of 9000 r / min for 8 min to allow the gold nanoparticles to self-assemble and grow, thereby obtaining a gold sol with partially agglomerated particles, but no gold flakes.
[0062] like Fig.11 As shown, the transmission electron microscopy of the gold nanospheres obtained in step (2) shows that the twinned gold nanospheres obtained in this comparative example have poor symmetry, and in addition to the exposed (111) plane, other crystal planes are exposed. Fig.12 As shown, the morphology of the sample obtained in step (3) under a scanning electron microscope shows that the gold nanospheres formed larger aggregates, but did not self-assemble to form the ideal nanoporous gold. This is because the high concentration of nanospheres may form aggregates prematurely, and the twin nanospheres have different exposed crystal faces, which is not conducive to the self-assembly of the particles.
Claims
1. A method for preparing nanoporous gold based on self-assembly growth of twinned gold nanospheres, characterized in that: Including twin gold nanosphere sol seed crystal preparation, twin growth and gold particle self-assembly growth: (1) Preparation of twin gold nanosphere sol seed crystals: Using tetrachloroauric acid solution and sodium citrate solution as raw materials, the twin gold nanosphere sol seed crystals are prepared by chemical reduction method; the concentration of the tetrachloroauric acid solution is 0.2-0.4 g / 100 ml, and the addition amount is 5-10 ml; the concentration of the sodium citrate solution is 0.5-1.5 wt%, and the addition amount is 4-5 ml; (2) Twinning growth: Continue to alternately add tetrachloroauric acid solution and sodium citrate solution to the twinned gold nanosphere sol seed crystals prepared in step (1) to carry out a reduction reaction, so that the grains grow to a desired size to obtain a gold sol; the concentration of the sodium citrate solution is 0.5 to 1.5 wt%, and the amount added each time is 1 to 3 ml; the concentration of the tetrachloroauric acid solution is 20 to 30 mmol / L, and the amount added each time is 0.5 to 2 ml; (3) Self-assembly growth of gold particles: The gold sol prepared in step (2) is centrifuged at a speed of 9000 to 12000 r / min for 8 to 20 minutes, and the grains self-assemble and grow under the action of centrifugal force to obtain the nanoporous gold.
2. The preparation method according to claim 1, characterized in that The preparation of the twinned gold nanosphere sol seed crystal comprises the following steps: adding a tetrachloroauric acid solution to boiling deionized water under stirring conditions, continuing to heat to boiling, then dripping a sodium citrate solution, continuing to heat and boil for 30 to 40 minutes, and naturally cooling to obtain a twinned gold nanosphere sol seed crystal with a grain diameter of 13 to 16 nm.
3. The preparation method according to claim 1, characterized in that: The twinning growth comprises the following steps: (1) stirring and heating the twinning gold nanosphere sol seed crystal to 85-95° C., then adding sodium citrate solution and tetrachloroauric acid solution, and continuously stirring and heating for 10-20 minutes; (2) Repeat step (1) 6 to 10 times to obtain a gold sol with a grain size of 25 to 35 nm.
4. The preparation method according to claim 1, characterized in that The diameter of the nanoporous gold is 2 to 4 mm.
Citation Information
Patent Citations
Immunodetection nanometer colloidal gold preparation method
CN105067807A
Preparing method capable of adjusting particle size of gold nanoparticles based on sodium citrate reduction method
CN106001606A
Manufacturing method of three-dimensional ordered porous microstructure and monolithic column prepared through same
CN107656327A